Metafiction, Pararealism and the "Canon" of Canadian Cinema - Knight, Deborah (Cinémas, 1992)
Critical thinking about the English-Canadian and Quebec cinemas has focused lo a large degree on the realist tendencies of our fiction filmmaking-tendencies, it is argued, which fiction filmaking has, historically inherited from Canadian documentary film practices. But in recent fiction filmmaking, Canadian filmmakers have moved beyond social realism. Indeed, the emergence in English-Canada and Quebec of filmmaking that is metafictional and pararealist — in films like Léa Pool's La Femme de l'hôtel, Bruce McDonald's Roadkill and Patricia Rozema's White Room — gives us occasion not only to rethink the criteria that have been used to identify "canonic" film, but more importantly to see how these self-conscious fictional strategies, which initially seem to reject the norms of social realism, are in fact part of an ongoing re-examination of the limits of fiction.